Comparison of experiment and theory for superelastic electron-collision studies from laser-aligned magnesium - Pursehouse, J.; Bostock, C.; Nixon, K.; Harvey, M.; Fursa, Dmitry; Bray, Igor; Murray, A. (2018)
A combined experimental and theoretical study of superelastic electron collisions from laser-aligned magnesium atoms for a range of collision energies from 35 to 55 eV is presented. Mg24 atoms were excited from the 3S01 ground state to the 3P11 excited state using continuous-wave linearly polarized laser radiation at ~285 nm. Electrons of well-defined energy Einc then deexcited the targets, and the superelastically scattered electrons emerging from the collision were detected as a function of scattering angle and laser polarization. Results for alignment of the target by the electron beam are presented for a range of scattering angles, for outgoing energies from Eout=35 to 55eV. The agreement between the measurements and the results of the convergent close-coupling theory are encouraging, but some discrepancies remain.